Supraclinoid internal carotid artery blister-like aneurysms: hypothesized pathogenesis and microsurgical clipping outcomes - Chen, Shanwen (Chin Neurosurg J, 2021)
BACKGROUND: Blister-like aneurysms (BLAs) on the supraclinoid segment of the internal carotid artery (ICA) are an enigma of cerebrovascular disease. Neither has a definite pathogenesis been so far identified, nor have uniform treatment guidelines been established for them. Our aim was to develop a hypothesis regarding the evolution of BLAs according to their macroscopic morphologies and to evaluate the efficacy of microsurgical clipping. METHODS: The clinical data and morphological features of 15 consecutive patients with 16 BLAs on the supraclinoid ICA were retrospectively reviewed. The treatment strategies were analyzed, and functional outcomes were evaluated using the modified Rankin scale (mRS). Favorable outcomes were defined as a mRS score of 0–2. RESULTS: Morphologically, aneurysm growth with expansion of the aneurysm neck before the surgical procedure occurred in two ruptured and one unruptured aneurysm. Daughter bleb formation was observed in two ruptured and five unruptured aneurysms. A varied degree of parent artery sclerosis was observed in nine patients. Thirteen patients were treated with direct surgical clipping, one patient was treated with clipping and wrapping, and the remaining patient was treated with an encircling clipping graft. Favorable and unfavorable outcomes were observed in 13 and two cases, respectively. Follow-up angiograms revealed 4 cases of stenosis with respective degree of mild, 30%, 50%, and 80% without any neurological dysfunction. CONCLUSIONS: We suggest a hypothesis that BLAs on the supraclinoid ICA may share different evolving mechanisms between ruptured and unruptured lesions. A majority of them can be reliably and safely obliterated by direct clipping technique, except for the aneurysms accompanied with severely atherosclerotic parent walls.